Kontribusi Religiusitas terhadap Perilaku Prososial Guru Sekolah Inklusi Berbasis Islam - Faza Dinan Hanifah; Stephani Raihana Hamdan (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2021)
The purpose of this study was to find the contribution of religiosity to prosocial behavior on teacher inclusion. This study is a causality study with the respondent of 74 teachers. The measuring instrument used was CRS-15 (The Centrality of Religiosity Scale) adapted by Wardhani (2015) to measure religiosity and The Prosocialness Scale for Adults by Caprara (2005) and adapted by a researcher to measure prosocial. The results showed that there is a significant correlation between religiosity and prosocial. Religiosity contributes 40.7% to the prosocial behavior.